The Gly16 Allele of the G16R Single Nucleotide Polymorphism in the β2-Adrenergic Receptor Gene Augments the Glycemic Response to Adrenaline in Humans - Rokamp, Kim Z.; Staalsø, Jonatan M.; Zaar, Morten; Rasmussen, Peter; Petersen, Lonnie G.; Nielsen, Rikke V.; Secher, Niels H.; Olsen, Niels V.; Nielsen, Henning B. (Frontiers in Physiology, 2017)
Cerebral non-oxidative carbohydrate consumption may be driven by a β2-adrenergic mechanism. This study tested whether the 46G > A (G16R) single nucleotide polymorphism of the β2-adrenergic receptor gene (ADRB2) influences the metabolic and cerebrovascular responses to administration of adrenaline. Forty healthy Caucasian men were included from a group of genotyped individuals. Cardio- and cerebrovascular variables at baseline and during a 60-min adrenaline infusion (0.06 µg kg-1 min-1) were measured by Model flow‚ near-infrared spectroscopy and transcranial Doppler sonography. Blood samples were obtained from an artery and a retrograde catheter in the right internal jugular vein. The ADRB2 G16R variation had no effect on baseline arterial glucose, but during adrenaline infusion plasma glucose was up to 1.2 mM (CI95: 0.36 – 2.1, P <0.026) higher in the Gly16 homozygotes compared with Arg16 homozygotes. The extrapolated steady-state levels of plasma glucose was 1.9 mM (CI95: 1.0 - 2.9, PNLME <0.0026) higher in the Gly16 homozygotes compared with Arg16 homozygotes. There was no change in the cerebral oxygen glucose index and the oxygen carbohydrate index during adrenaline infusion and the two indexes were not affected by G16R polymorphism. No difference between genotype groups was found in cardiac output at baseline or during adrenaline infusion. The metabolic response of glucose during adrenergic stimulation with adrenaline is associated to the G16R polymorphism of ADRB2, although without effect on cerebral metabolism. The differences in adrenaline-induced blood glucose increase between genotypes suggest an elevated β2-adrenergic response in the Gly16 homozygotes with increased adrenaline-induced glycolysis compared to Arg16 homozygotes.